A Novel Antimicrobial–Phytochemical Conjugate With Antimicrobial Activity Against Streptococcus uberis, Enterococcus faecium, and Enterococcus faecalis - Rajamanickam, Karthic; Yang, Jian; Sakharkar, Meena Kishore (Frontiers in Pharmacology, 2019)
Antimicrobial resistance is one of the major threats to human and animal health. An effective strategy to reduce and/or delay antimicrobial resistance is to use combination therapies. Research in our laboratory has been focused on combination therapies of antimicrobials and phytochemicals and development of antimicrobial-phytochemical conjugates. In this study, we report the synthesis and antimicrobial activity of a novel sulfamethoxazole-gallic acid conjugate compound (Hybrid 1). Hybrid 1 not only showed much stronger activity than sulfamethoxazole towards Streptococcus uberis 19436, Enterococcus faecium 700221 and Enterococcus faecalis 29212, which were purchased from American Type Culture Collection (ATCC), but also exhibited a promising antimicrobial effect against two Enterococcus faecalis clinical isolates, one of which was multidrug resistant. Further studies are warranted to establish the in vivo antimicrobial activity for Hybrid 1 and develop more potent sulfamethoxazole-gallic acid based antimicrobial conjugates using Hybrid 1 as a lead compound.